Theoretical Insights into Tendencies in Social Practice Art - Vilutyte, Zita (Jaunųjų mokslininkų darbai, 2019)
The paper deals with tendencies in and opportunities for social practice art. The concept of social practice art in an international context and its tendencies abroad and Lithuania have been studied. The aim is to provide theoretical insights into the forms of social practice art and to study its development tendencies.Social practice art (SPA) is an artistic tool oriented to common activities of artists and various social groups through social discourse. SPA rose as a response to a growing need for artistic education while collaborating with social groups in a multicultural environment. Growing numbers of artists, curators, critics and art administrators worldwide have been focusing on a new type of artistic activities - the so-called art activism. One type of such activism is characterized by the term social practice art. These activities are aimed at positive changes in particular communities in the face of relevant issues: racism, urban gentrification, environmental damage, unstable working conditions, high levels of imprisonment, global refugee influx, etc.Artists engaged in social practice art collaborate with a particular audience or run critical interventions in the existing social systems - all that sparks off debates or promotes social exchange. It is a new phenomenon in Europe, but has already found its place in many countries where a strong creative class, flows of moving migrants, a large class exclusion exist - in the UK, Germany, the Netherlands and many others. In Lithuania, the problem of social art assessment was tackled analyzing the project “Shanciai - Friendly Zone” run in Kaunas (Dovydaitytė, 2014). This study discusses the principles of social practice art assessment. New opportunities arise in various parts of the world, thus, seeking to open up their potential, it is important to study the development of this promising activity.
Keywords: social practice art; SPA; multiculture; innovation; activism